2015
DOI: 10.1021/acs.jpcc.5b07325
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Induced Molecular Rearrangement of an Ionic Liquid Confined in Nanospaces: An in Situ X-ray Absorption Fine Structure Study

Abstract: A temperature-dependent X-ray absorption fine structure (XAFS) study was performed to investigate structural changes in the 1-hexyl-3-methylimidazolium bromine (C 6 mimBr) ionic liquid (IL) confined within the channels of multiwalled carbon nanotubes (MWCNTs). The XAFS spectra at room temperature confirmed the charge transfer from the bromine anion of the encapsulated IL to the MWCNTs. R-space analysis at ambient temperature revealed the reduced distance between the anions and cations in the confined IL compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…Their results indicate a confinement-induced melting temperature shift of the studied ILs, which agrees well with the experimental observations . A similar temperature-induced structural transformation was also reported for the 1-hexyl-3-methylimidazolium bromine ([C 6 mim]­Br) IL confined in carbon nanotubes . Despite the progress, little has been reported about the structure–spectra relationship of confined ILs.…”
Section: Introductionsupporting
confidence: 87%
“…Their results indicate a confinement-induced melting temperature shift of the studied ILs, which agrees well with the experimental observations . A similar temperature-induced structural transformation was also reported for the 1-hexyl-3-methylimidazolium bromine ([C 6 mim]­Br) IL confined in carbon nanotubes . Despite the progress, little has been reported about the structure–spectra relationship of confined ILs.…”
Section: Introductionsupporting
confidence: 87%
“…Common experimental techniques include AFM, 116 123 scanning tunneling microscopy (STM), 124 , 125 differential scanning calorimetry, 126 , 127 NMR, 128 132 high-resolution TEM, 133 135 thermogravimetric analysis, 13 and X-ray diffraction. 126 , 136 In addition to direct experimental observations, researchers often use theoretical simulations to study the influence mechanism of e.g. the substrate shape, material, and applied electric field on the structures, properties, and functions of interfacial ILs.…”
Section: From the Bulk To The Interface: Z-bonds → Quasi-liquidsmentioning
confidence: 99%
“…100 K in comparison with that of bulk ILs. 126 , 135 Theoretical simulations 169 indicated that disordered bulk BmimBF 4 adopts an ordered microcrystal structure, inducing an abnormal enhancement of the melting point. Furthermore, the melting point of confined EmimPF 6 further increases with a decreasing radius of the CNT.…”
Section: From the Bulk To The Interface: Z-bonds → Quasi-liquidsmentioning
confidence: 99%
“…This can be explained as follows. Normally, RS is sensitive to nonpolar vibration such as vibration of the C-C bond [64]. In this case, for muscovite, the spectrum mainly reflects Si-O or Al-O vibration.…”
Section: Resultsmentioning
confidence: 99%